TECHNOLOGY BASED ON SODIUM ALKALINE ROASTING AND HYDROMETALLURGICAL METHODS OF MANGANESE EXTRACTION FROM SLAGS OF THE STEELING INDUSTRY - Parmonov Sarvar Toshpulatovich; Mirzavaliyev Dostonbek Baxodir o‘g‘li; Sattorqulov Xasan Doniyor o‘g‘li (Web of Journals Publishing, 2025)
This article analyzes the technology of sodium hydroxide roasting and hydrometallurgical processing for extracting manganese from metallurgical slags. The study tested methods for obtaining a selective solution from slag samples roasted at temperatures of 200°C and 300°C using distilled water and 16% sulfuric acid. Based on EDXRF and XRD analyses, manganese compounds with a purity of up to 34% were isolated, and the ecological and economic advantages of this method were substantiated.
Keywords: manganese, metallurgical slag, sodium hydroxide, hydrometallurgy, sulfuric acid, EDXRF, selective leaching